A case report of IPEX syndrome in Palestine: detailed family identification and breadth of disorders with the same defect - Malhis, Lana; AbdalSalam, Zeidan; Njoum, Yumna; Abdelhaq, Anan; Sharaf, Muna (Frontiers in Pediatrics, 2024)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a monogenic disorder characterized by multi-systemic autoimmunity secondary to loss-of-function mutations in the gene coding the forkhead box P3 (FOXP3) transcription factor which is important for the development, maturation, and maintenance of CD4+ regulatory T (T-reg) cells. Fewer than 300 affected individuals have been identified worldwide. The occurrence of IPEX is below 1:1,000,000. Herein we present a case of a 15-day-old male who was admitted to NICU 15 days after delivery due to respiratory distress. He was found to have metabolic acidosis due to DKA. During his stay in the NICU, he experienced seizures and was intubated for a month. He was diagnosed with neonatal diabetes. He also experienced recurrent respiratory infections and multiple episodes of diarrhea rash, and meningitis. At the age of 7 months, genetic testing confirmed IPEX with FOXP3 mutation, specifically the p.(Pro75Leu) variant of the FOXP3 gene. Subsequently, multiple family members were diagnosed. The unique variability observed in organ involvement and presentation timing among individuals within the same family, despite carrying an identical mutation, is a distinctive aspect, particularly considering the monoallelic expression of the FOXP3 gene in males. This phenomenon strongly suggests the presence of modifying genes that play a significant role in the pathogenesis of IPEX syndrome. The case presentation underscores the importance of clinical suspicion of IPEX in cases of neonatal DM. It also highlights the challenges associated with managing rare genetic disorders in pediatric patients. It also emphasizes that the IPEX genotype has a wide phenotype. This case is considered the first documented case of IPEX in Palestine.